Sleep environments of Japanese adolescents: An epidemiological study. Issue 2 (25th February 2014) - Ikeda, Maki; Kaneita, Yoshitaka; Yamamoto, Ryuichiro; Itani, Osamu; Kondo, Shuji; Osaki, Yoneatsu; Kanda, Hideyuki; Higuchi, Susumu; Ohida, Takashi
Abstract We conducted an epidemiological study to examine the associations between sleep environments and sleep habits in Japanese adolescents. The targets were students attending junior and senior high schools throughout Japan. Sample schools were selected by cluster sampling. Self‐reported anonymous questionnaires were then sent to the schools for all students to complete. A total of 99 416 adolescents responded, with an overall response rate of 64.0%. A total of 96 861 questionnaires were subjected to analysis. Associations between sleep environments (type of bed, lighting during sleep, sharing a bedroom) and sleep duration, bedtimes, wake‐up times, sleep quality, or symptoms of insomnia were examined. In total, 65.5% of the adolescents surveyed slept on a bed, and 33.0% slept on a futon laid on the floor or tatami. In total, 66.6% slept with the light off, 31.0% slept with a dim light on, and 2.0% slept with the light on. Of those surveyed, 69.3% had their own bedrooms, 17.1% shared a bedroom with one other person, 8.0% shared a bedroom with three people, and 5.0% shared a bedroom with four people or more. The factors with high odds ratios with regard to insomnia were use of a futon laid on the floor or tatami, sleeping with the light on, and not sharing a bedroom. Sleep environments are associated with insomnia. Type of bed, lighting, and sharing a bedroom should be considered as factors that affect the sleep of adolescents.